The impact of alibaba's global e-commerce training (get) program towards utar students - Low, Zhi Qing (2025)
This study investigates the impact of Alibaba’s Global E-Commerce Training (GET) Program towards UTAR students. The impact of entrepreneurial self-efficacy, entrepreneurial mindset, digital competency and entrepreneurial intention influenced by the GET Program is examined using Theory of Planned Behaviour. Using a Google Form and judgemental sampling, a total of 129 valid respondents were surveyed. The purpose of the study is to investigate how Alibaba’s GET Program influenced the entrepreneurial intentions of UTAR students.